2006
DOI: 10.1007/s00412-005-0046-0
|View full text |Cite
|
Sign up to set email alerts
|

Cenp-F (mitosin) is more than a mitotic marker

Abstract: Cenp-F (mitosin) is a large coiled-coil protein whose function has remained obscure since its identification a decade ago. It has been suggested that the protein plays a role in the kinetochore-mediated mitotic functions but until recently there was little evidence to support this postulation. Recent results from five laboratories have given insights on how Cenp-F may participate in the regulation of cell division. In this mini-review, we will summarize the current data regarding the mitotic tasks of Cenp-F as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 63 publications
2
89
0
3
Order By: Relevance
“…Although CENPF is initially known for its association with the centromere-kinetochore complex and chromosomal segregation, previous studies have demonstrated that CENPF may play a role in the regulation of the mitosis and proliferation of malignant cell growth, which are mediated by protein interactions (13,(29)(30)(31)(32). Thus, the actual functional role of CENPF is more elusive and complex.…”
Section: Irs Of Cenpf In Our Cohortmentioning
confidence: 99%
See 2 more Smart Citations
“…Although CENPF is initially known for its association with the centromere-kinetochore complex and chromosomal segregation, previous studies have demonstrated that CENPF may play a role in the regulation of the mitosis and proliferation of malignant cell growth, which are mediated by protein interactions (13,(29)(30)(31)(32). Thus, the actual functional role of CENPF is more elusive and complex.…”
Section: Irs Of Cenpf In Our Cohortmentioning
confidence: 99%
“…Centromere protein F (CENPF), at chromosome 1q41, is one of these 31 genes. It encodes a protein that acts as part of the centromere-kinetochore complex and is a component of the nuclear matrix during the G2 phase of interphase (13). CENPF is expressed in a cell cycle-dependent manner and is involved in chromosome segregation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nup133 recruits CENP-F both at the kinetochore (Zuccolo et al, 2007) and the prophase NPC. CENP-F then recruits CENP-E and dynein at the kinetochore (Varis et al, 2006;Mao et al, 2010). Similarly, at the prophase NPC, CENP-F recruits the dynein/dynactin complex via NudE and NudEL.…”
Section: Microtubule Attachment To the Npc-associated Y-complexmentioning
confidence: 99%
“…It functions in a cell cycle manner, present as a nuclear matrix protein during interphase then redistributing during early G2 of the cell cycle [1][2][3][4]. Since its discovery in 1993, a number of its functions have been elucidated, including involvement in centromere maturation, regulation of metaphase checkpoint and ensuring appropriate orientation of chromosomes [4][5][6][7][8][9]. Furthermore, it is involved in the attenuation of histone methylation and negative regulation of activating transcription factor-4 (ATF4), a transcription factor important for stress proliferation and differentiation of cells [1,10].…”
Section: Introductionmentioning
confidence: 99%